5x-2(x-4)=-9+5x+13

Simple and best practice solution for 5x-2(x-4)=-9+5x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2(x-4)=-9+5x+13 equation:



5x-2(x-4)=-9+5x+13
We move all terms to the left:
5x-2(x-4)-(-9+5x+13)=0
We add all the numbers together, and all the variables
5x-2(x-4)-(5x+4)=0
We multiply parentheses
5x-2x-(5x+4)+8=0
We get rid of parentheses
5x-2x-5x-4+8=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2

See similar equations:

| 1/4x-1=1/5x | | 2x-3=-(4×+9 | | X+.40x=49 | | 5x+3+62=180 | | 23+5n+4n-13=10n+16-n-6 | | 0.5(w-8)=2 | | 8y-3y=15+2y | | 1x-24+29=296 | | 3/2(2x-4)-3=-12 | | -12=-4(6x-3) | | -(5n-15)=-5(n+4) | | -7+11x=-5x | | 6(-7v+3)+6=234 | | (11,31)m=0 | | -3/5y=4 | | 4x^2+(4x)^2=20 | | 4x+20=-8x-28 | | |4t-3|=7 | | 4x+8=2x(2x+4) | | -13.1=2.2x+4.5 | | 6+4(3x-6)=5-3(2x+1) | | 50+2x=80 | | 36=13n−4n36=13n−4n. | | -5=3m- | | 3x-1/2=5x+2/3+1 | | -5=2(10b-2)=31 | | 4x+8=2x(2x-4) | | 4x+8=2x(2x-8) | | -6(4x-5)+5(5x-3)-2=6-7 | | 180-x=3×(90-x)+30 | | 2/h-1/3h+11=8 | | 6x-1/6=9 |

Equations solver categories